Сentral heamodynamic сondition and morphological characteristics of lungs at patients with lung cancer depending on components of the infusion-transfusion therapy. - Tverdokhlib, I. V.; Novikov, S. P. (Морфологія / Morphologia / Morfologìâ, 2015)
Background. Despite the large number of studies devoted to the study of the functional state of the cardiovascular and respiratory systems after operations on the lungs, there are still many issues regarding the mechanisms of hemodynamic disorders in the postoperative period. It stipulates considerable difficulties in the treatment and prevention of functional disorders of respiration and circulation. Objective. The aim of this study is to determine the central hemodynamics parameters depending on the condition of ventilate lung function in thoracic oncology patients during the postoperative period and to determine the morphological features of the lungs that developed under the influence of intraoperative administration of refortan and perftoran. Methods. The condition of the central heamodynamic and morphological features of the lungs at patients with lung cancers with different level of the ventilating respiratory insufficiency in the early postoperative period after application of 3 and 1,5 ml/kg of perftoran and after traditional refortan (5 ml/kg) infusion-transfusion therapy were determined. Results and conclusion. It was proved that perftoran is much more effective than pefortan. The restoration of the normodynamic type of heamodynamic after infusion of perftoran (1,5 ml/kg) to patients with the an initial level of the ventilating respiratory insufficiency of I and II degree is observed during 1st postoperative week. The restoration of the normodynamic type of heamodynamic at to patients with the initial level of the ventilating respiratory insufficiency of III degree in postoperative period is reached by using perftoran in a dose 3 ml/kg. In the dead after pneumonectomy with intraoperative administration of perftoran there is increasing of synthetic activity of alveolocyte type II along with compensatory microcirculatory changes.